Applying inductive-deductive reasoning to the resolution of a mathematical proof problem - Álvarez Esteven, Juan; Alonso Berenguer, Isabel; Gorina Sánchez, Alexander (Transformación, 2024)
Objective: The paper aims at illustrating mathematics problem solving through a method devised by the authors based on the inductive interpretation of the problem and on the inductive-deductive reasoning. Methods: The methodology used to conduct the research combines qualitative and quantitative methods by means of an alternative developed by Álvarez, Alonso, & Gorina (2018) that integrates exploratory-inductive, validating-inductive and demonstrating-deducting procedures. Results: The study proves that the devised method is distinguished by its emphasis on the relation between the interpretative statement, the inductive generalization of the speculated solution and its deductive validation Conclusion: The authors arrived at the conclusion that the illustrated method positively influences the development of students’ mathematical problem-solving skills.